(untitled) (Research, Society and Development, 2020)
Elementary Education, as well as Early Childhood and Secondary Education, aims to develop in the student the ability to learn, the understanding of the natural and social environment and the strengthening of the bonds on which social life is based. The objective of this work is to quantify the number of enrollments in Special Education, in the initial and fundamental years, in the State of Amapá, Brazil, between 2015 and 2018. The approach of this study is quanti-qualitative. To this end, a search was conducted in the database of the National Institute of Educational Studies and Research Anísio Teixeira (INEP), and the subsequent discussion of the data, based on documents and bibliographies. From the data and variables provided, it can be seen that the absence of official data, makes it difficult to support studies that allow greater depth in the topic of school dropout in Special Education, and, consequently, better evaluate public policies of insertion for the target audience. of this teaching modality. To equitably insert special students, it is necessary that most schools have Specialized Educational Services, and that they be distributed equally within the neighborhoods, in their respective municipalities to reach the largest possible number of students. As well as building the specific terminality for each special need, as well as minimizing the weaknesses that special students face in the educational process and, consequently, reducing the dropout rates of people with disabilities.